A Unique Single‐Ion Mediation Approach for Crossover‐Free Nonaqueous Redox Flow Batteries with a Na+‐Ion Solid Electrolyte. Issue 1 (13th November 2019) - Yu, Xingwen; Yu, Wiley A.; Manthiram, Arumugam
Abstract: Nonaqueous redox flow batteries (RFBs) provide significant advantages over aqueous RFBs because the use of nonaqueous electrolytes offers the possibilities of operating RFBs at higher voltages (above the water break‐down voltage) and low temperatures (below 0 °C, the freezing point of H2 O). However, the advancement of RFBs has long been plagued by the chemical‐crossover problem due to a lack of reliable separators. Herein, a single‐ion mediation strategy is presented for the advancement of nonaqueous RFBs by employing a Na + ‐ion solid electrolyte. The catholyte and anolyte in a single cell are physically and electrically separated, but the redox reactions at the cathode and anode are ionically linked by sodium ions, which shuttle between the catholyte and anolyte through the solid electrolyte. To accommodate the mediating Na + ‐ions, both the catholyte and anolyte are well managed through the addition of appropriate supporting electrolytes. The proposed unique RFB concept is validated with a chromium (III) acetylacetonate symmetric redox chemistry and the nitrobenzene–bromine redox couple. Abstract : A single‐ion mediation strategy enables the advancement of crossover‐free nonaqueous redox flow batteries by employing a Na + ‐ion solid electrolyte.